PENGARUH RETURN ON ASSET, GROWTH, TOTAL ASSET TURNOVER, OWNERSHIP, FIRM SIZE DAN DEBT TO TOTAL ASSET TERHADAP DIVIDEND PAYOUT RATIO PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2010-2012 - Sandra Meilina Simanjuntak (POLITEKNIK LP3I JAKARTA, 2016)
ABSTRACT Dividend Payout Ratio is the guidelines established by the company to determine the amount of money that will be paid out as a dividend to investors .There are many factors that could affect dividend policy . In this study, the independent variables used were Return on Assets , Growth , Total Asset Turnover, Ownership , Firm Size and Debt to Total Assets . This study used 60 companies were listed in the Indonesia Stock Exchange during the period 2010-2012 . Data downloaded from the internet via the official website later www.idx.com financial statements of listed companies to be taken in the selection of data companies thatonly distribute dividends during the period 2010-2012 alone. Keyword : Financial Ratio, Dividend Payout Ratio